Development and Performance Evaluation of a Gel-Based Plugging System for Complex Fractured Formations Using Acrylic Resin Particles - Lei Yao; Xiaohu Quan; Jihe Ma; Ge Wang; Qi Feng; Hui Jin; Jun Yang (Gels)
The issue of fluid loss in fractured formations presents a significant challenge in petroleum engineering, often leading to increased operational costs and construction risks. To address the limitations of traditional lost circulation materials (LCMs) in oil reservoirs with different fracture sizes, this study developed an acrylic resin gel particle with excellent thermal stability (thermal decomposition temperature up to 314 °C) and compatibility. By employing Box–Behnken design and response surface methodology, the synergistic interaction of calcium hydroxide (Ca(OH)2), asbestos fibers, and cement was optimized to create a novel gel solidification plugging system that meets the requirements of fluid loss control and compressive strength improvement. Experimental results revealed that the gel-based system demonstrated exceptional performance, achieving rapid fluid loss (total fluid loss time of 18~47 s) and forming a high-strength gelled filter cake (24 h compressive strength up to 17.5 MPa). Under simulated conditions (150 °C), the gel-based system provided efficient fracture sealing, showcasing remarkable adaptability and potential for engineering applications. This study underscores the promise of acrylic resin gel particles in overcoming fluid loss challenges in complex fractured formations.